Reading First Initiative in Rural Pennsylvania Schools - Jaqueline Edmondson; Patrick Shannon (Journal of Research in Rural Education, 2003)
The reading, First Initiative, as part of the No Child Left Behind Act of 2001, specifically targets poor schools with low test scores in reading. Reading First in Pennsylvania is a 6-year, $184 million compettive grant program. In 2002-2003, 13 of the 28 funded schools were rural. In this article, we consider how the Reading First policy is experienced in one rural Pennsylvania school, and we raise questions about the conditions and consequences of his legislation in relation to this school's experience.